A Bifunctional Nano‐Electrocatalyst Based on a Flower‐like Gold/Palladium Bimetallic Alloy Nanostructure and Its Graphene Hybrid. Issue 24 (25th September 2015) - Sahu, Subash Chandra; Satpati, Biswarup; Besra, Laxmidhar; Jena, Bikash Kumar
Abstract: This work demonstrates the one‐pot, seed‐free synthesis of unique flower‐like Au/Pd alloy nanostructures and their self‐assembly on a graphene support in an aqueous medium. The as‐prepared nanostructures were characterized thoroughly by TEM, UV/Vis spectrophotometry, XRD, and X‐ray photoelectron spectroscopy (XPS). The bifunctional electrocatalytic activity towards the oxidation of methanol and reduction of oxygen was investigated thoroughly. The results reveal that the Au/Pd alloy nanostructures show a composition‐dependent electrochemical activity. The Au/Pd alloy nanostructure with a flower‐like morphology shows superior electrocatalytic activity compared to its monometallic Pd counterpart and a commercially available Pd/C. Furthermore, the graphene support tunes the electrocatalytic performance of the Au/Pd alloy nanoflowers and substantiates their promising energy‐conversion applications for use in fuel cells. Abstract : Flower power : The synergetic effect of graphene and the unique flower‐like structure of the Au/Pd alloy tunes the electrocatalytic performance towards the oxidation of methanol and the reduction of oxygen, which paves the way for the application of this material in fuel cells.